2019
DOI: 10.1016/j.ijmachtools.2019.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Laser Powder Bed Fusion of Ti-rich TiNi lattice structures: Process optimisation, geometrical integrity, and phase transformations

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 112 publications
(42 citation statements)
references
References 51 publications
1
35
0
Order By: Relevance
“…Recently, PBF has become widely adopted in many industrial applications, offering advantages when compared to traditional manufacturing such as versatility and accuracy, as well as the ability to produce functional components. The technology demonstrated a great capability to process NiTi with high repeatability [ 43 , 44 ]. To improve the functionality of auxetic materials, shape memory alloys (SMA) such as NiTi can be used to combine the properties of the material to the unique behavior of the structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, PBF has become widely adopted in many industrial applications, offering advantages when compared to traditional manufacturing such as versatility and accuracy, as well as the ability to produce functional components. The technology demonstrated a great capability to process NiTi with high repeatability [ 43 , 44 ]. To improve the functionality of auxetic materials, shape memory alloys (SMA) such as NiTi can be used to combine the properties of the material to the unique behavior of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…NiTi SMAs exhibit motor-functionalities due to a reversible phase transformation from martensite to austenite and vice versa, which can be triggered by temperature (shape memory effect) or deformation (superelasticity). This motor-functionality makes NiTi suitable for energy-absorption, and actuating and inflatable devices as they can be actuated to their initial shape when deformed, with or without the aid of external heat [ 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that by introducing an engineered level and type of porosity to a bone fixation plate, one is able to further reduce the stiffness of NiTi bone fixation plates and reach the level of bone tissue [15,16]. We have also shown that the additive manufacturing method, in the form of selective laser melting (SLM), can be used for the fabrication of porous NiTi bone fixation plates [17,18]. Although we have shown successful results in different sections of this novel approach, in this article with a focus on the fabrication approach (i.e., additive manufacturing), we characterized the fabricated parts and updated the design methodology based on that.…”
Section: Introductionmentioning
confidence: 99%
“…This is mostly due to the freedom of fabrication and the superior properties of NiTi, as mentioned earlier. However, most of the research is fundamental, aimed at finding optimal fabrication process parameters and their effects on the part's properties [31], lattice structures [18], corrosion behavior [3], modeling [32], and biocompatibility [33]. It should also be noted that all the SLM fabricated porous structures in the literature have been evaluated only in compression mode and no study, as far as we know, has been done on a realistic stiffness-matched porous bone fixation plate, which is under tension.…”
Section: Introductionmentioning
confidence: 99%
“…Additive Manufacturing (AM), as a netshape technology, has developed rapidly in the past 10 years. Recent interest in the processing of more expensive materials has been driven by the ability of the technique to potentially reduce material waste [1][2][3][4]. Selective Laser Melting (SLM) is an AM process that uses a high intensity laser to selectively melt defined areas geometries layer by layer and therefore allows the production of near netshape components directly from the metal powder [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%